How Transgender and Gender Expansive Youth Cope with Oppression: Making Sense of Experiences and Resiliency Factors. Issue 1 (1st February 2023) - Saltis, Michelle N.; Critchlow, Claire; Fulling-Smith, Jennifer
Abstract: This manuscript is a part of a four-manuscript series that shares the findings from the first known Interpretative Phenomenological Analysis (IPA) study on how transgender and/or gender expansive youth (TGEY) experienced their gender identities and additional intersecting identities within the context of current political, social, cultural, and historical factors. This manuscript explores the resiliency and meaning-making factors of TGEY. Data was collected through two 60–90-minute semi-structured interviews. Within this overarching theme of resiliency factors, two sub-themes emerged that focused on the participants' creativity, and the ways they engaged in activism and education.